Formative Feedback in Blackboard Learn Environment for College Academic Literacy of Engineering Students (LACCEI, 2024)
The COVID-19 pandemic spread the virtual mode to the masses through various learning platforms. In higher education, the possibilities offered by these platforms were used to innovate evaluation in e-learning environments. Due to the formative needs of engineering students regarding academic writing, the objective of the research is to determine the impact of virtual formative feedback on the academic literacy of engineering students in a writing course with the support of the Learning environments in LMS Blackboard. The study corresponds to a pre-experimental investigation in a sample made up of 39 students. The Wilcoxon signed rank test gave an overall value of -5.388b with a value of p=0.000. Therefore, it demonstrates that formative feedback has a positive impact on the development of academic literacy in the Blackboard virtual environment.